2020
DOI: 10.1021/jacs.0c10486
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Coupling in Chemically Fueled Assembly: A Reaction Cycle Regulates Self-Assembly and Vice Versa

Abstract: In biology, self-assembly of proteins and energy-consuming reaction cycles are intricately coupled. For example, tubulin is activated and deactivated for assembly by a guanosine triphosphate (GTP)-driven reaction cycle, and the emerging microtubules catalyze this reaction cycle by changing the microenvironment of the activated tubulin. Recently, synthetic analogs of chemically fueled assemblies have emerged, but examples in which assembly and reaction cycles are reciprocally coupled remain rare. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(95 citation statements)
references
References 53 publications
5
90
0
Order By: Relevance
“…Moreover, coupling catalysis to a dissipative CRN containing assembling products could give rise to unusual assembly behaviour and feedback. [26][27][28]44 Here, instead of using enzymes, with limited operational stability and high specicity, it would be recommended to start exploring small molecules and metal catalysts. This way organocatalysis in combination with metal catalysis in non-natural systems can play similar roles as enzymes in nature and provide new systems with a high degree of control and an adaptive character.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Moreover, coupling catalysis to a dissipative CRN containing assembling products could give rise to unusual assembly behaviour and feedback. [26][27][28]44 Here, instead of using enzymes, with limited operational stability and high specicity, it would be recommended to start exploring small molecules and metal catalysts. This way organocatalysis in combination with metal catalysis in non-natural systems can play similar roles as enzymes in nature and provide new systems with a high degree of control and an adaptive character.…”
Section: Perspective and Outlookmentioning
confidence: 99%
“…Supramolecular polymers offer stimuli-responsive optical, [1][2][3][4][5] mechanical, [6][7][8][9] or out-of-equilibrium behaviors that emerge from molecular organization. [10][11][12][13] The ability to leverage these properties will benefit from developing tunable systems whose assemblies are mechanically and chemically robust, yet remain reversible and responsive. Recently, we found that imine-linked macrocycles (ca.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a population of transient product molecules emerges whose properties are regulated kinetically. In recent years, examples of such reaction cycles have been introduced that regulate the ability of molecules to assemble or phase separate, resulting in dynamic structures like colloids, 8,9 fibers, [9][10][11][12][13][14][15] oil-based droplets, 16,17 coacervate-based droplets, 18,19 vesicles, [20][21][22] micelles, 23 particle clusters, [24][25][26][27] macrocycles 28 and DNA-based nanostructures. 29,30 Due to the transient nature of these building blocks, these assemblies are endowed with properties we do not typically encounter at equilibrium.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, examples of such assemblies were found that exert feedback over their chemical reaction cycle. 10,23,36,37 The underlying mechanisms can result in exciting behavior like the spontaneous emergence of switches between the morphologies or the ability of molecules to persist while others decay. 8,16 All these developments in the field are incremental steps towards the synthesis of life, and a living system essentially represents a complex non-equilibrium assembly of molecules that is regulated by chemical reaction cycles.…”
Section: Introductionmentioning
confidence: 99%